Epistasis and the sensitivity of phenotypic screens for beta thalassaemia. (17th December 2014) - Penman, Bridget S.; Gupta, Sunetra; Weatherall, David J.
Summary: Genetic disorders of haemoglobin, particularly the sickle cell diseases and the alpha and beta thalassaemias, are the commonest inherited disorders worldwide. The majority of affected births occur in low‐income and lower‐middle income countries. Screening programmes are a vital tool to counter these haemoglobinopathies by: (i) identifying individual carriers and allowing them to make informed reproductive choices, and (ii) generating population level gene‐frequency estimates, to help ensure the optimal allocation of public health resources. For both of these functions it is vital that the screen performed is suitably sensitive. One popular first‐stage screening option to detect carriers of beta thalassaemia in low‐income countries is the One Tube Osmotic Fragility Test (OTOFT). Here we introduce a population genetic framework within which to quantify the likely sensitivity and specificity of the OTOFT in different epidemiological contexts. We demonstrate that interactions between the carrier states for beta thalassaemia and alpha thalassaemia, glucose‐6‐phosphate dehydrogenase deficiency and Southeast Asian Ovalocytosis have the potential to reduce the sensitivity of OTOFTs for beta thalassaemia heterozygosity to below 70%. Our results therefore caution against the widespread application of OTOFTs in regions where these erythrocyte variants co‐occur.